A Link Between Mitochondrial Dysfunction and the Immune Microenvironment of Salivary Glands in Primary Sjogren’s Syndrome - Li, Ning; Li, Yusi; Hu, Jiawei; Wu, Yicheng; Yang, Jie; Fan, Hongmei; Li, Lei; Luo, Danyang; Ye, Yulin; Gao, Yiming; Xu, Haimin; Hai, Wangxi; et al. (Frontiers in Immunology, 2022)
Background Primary Sjogren’s syndrome (pSS) is a slowly progressive, inflammatory autoimmune disease characterized by lymphocytic infiltration into salivary and lacrimal glands. It becomes more recognized that morphology alterations of epithelial mitochondria are involved in altered cellular bioenergetics in pSS patients. The integrated analysis of the mitochondrial role in the pathogenesis and aberrant immune microenvironment in pSS remains unknown. Methods The mitochondria-related genes and gene expression data were downloaded from the MitoMiner, MitoCarta, and NCBI GEO databases. We performed novel transcriptomic analysis and constructed a network between the mitochondrial function and immune microenvironment in pSS-salivary glands by computer-aided algorithms. Subsequently, real-time PCR was performed in clinical samples in order to validate the bioinformatics results. Histological staining and transmission electron microscopy (TEM) were further studied on labial salivary gland samples of non-pSS and pSS patients characterized for mitochondria-related phenotypic observation in the different stages of the disease. Results The bioinformatic analysis revealed that the expression of several mitochondria-related genes was altered in pSS. Quantitative real-time PCR showed that four hub genes, CD38, CMPK2, TBC1D9, and PYCR1, were differentially expressed in the pSS clinical samples. These hub genes were associated with the degree of immune cell infiltration in salivary glands, the mitochondrial respiratory chain complexes, mitochondrial metabolic pathway in gluconeogenesis, TCA cycle, and pyruvate/ketone/lipid/amino acid metabolism in pSS. Clinical data revealed that the gene expression of fission (Fis1, DRP1, and MFF) and fusion (MFN1, MFN2, and OPA1) was downregulated in pSS samples, consistent with the results from the public validation database. As the disease progressed, cytochrome c and Bcl-2 proteins were regionally distributed in salivary glands from pSS patients. TEM revealed cytoplasmic lipid droplets and progressively swollen mitochondria in salivary epithelial cells. Conclusion Our study revealed cross talk between mitochondrial dysfunction and the immune microenvironment in salivary glands of pSS patients, which may provide important insights into SS clinical management based on modulation of mitochondrial function.